Management Strategies for the Mangrove Crab (Scylla spp) Fishery Business in Bula Air Village, East Seram Regency - Walla, Siti Aisa; Nanlohy, Helen; Lopulalan, Yoisje (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
This study aims to analyze the management strategies of the mangrove crab (Scylla spp) fishery business in Bula Air Village, East Seram Regency. The study focuses on identifying the challenges, potential, and opportunities for sustainable business development. The research used primary data collection methods, including interviews, field observations, and Focus Group Discussions (FGD), along with secondary data from supporting literature. The results indicate that the mangrove crab fishery business in Bula Air Village contributes significantly to the local community's income but faces various challenges, such as limited post-harvest facilities, insufficient fishing gear, and long marketing chains. The Internal-External (IE) Matrix analysis shows that this business is positioned in the